Detection of volatile organic compounds using a polythiophene derivative - Goncalves, V. C.; Nunes, B. M. [UNESP]; Balogh, D. T.; Olivati, C. A. [UNESP] (Wiley-v C H Verlag Gmbh, 2010)
Conjugated polymers have been subject of great interest in the recent literature from both fundamental point of view and applied science perspective. Among the several types of conjugated polymers used in recent investigations, polythiophene and its derivatives have attracted considerable attention over the past 20 years due to their high mobility and other remarkable solid-state properties. They have potential applications in many fields, such as microelectronic devices, catalysts, organic field-effect transistors, chemical sensors, and biosensors. They have been studied as gas and volatile organic compounds (VOCs) sensors using different principles or transduction techniques, such as optical absorption, conductivity, and capacitance measurements. In this work, we report on the fabrication of gas sensors based on a conducting polymer on an interdigitated gold electrode. We use as active layer of the sensor a polythiophene derivative: poly (3-hexylthiophene) (P3HT) and analyzed its conductivity as response for exposure to dynamic flow of saturated vapors of six VOCs [n-hexane, toluene, chloroform, dichloromethane, methanol, and tetrahydrofuran (THE)]. Different responses were obtained upon exposure to all VOCs, THF gave the higher response while methanol the lower response. The influence of moisture on the measurements was also evaluated. (C) 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim
Keywords: conjugated polymers; electrical properties; sensors